Clinical treatment of wounds using nano platelet-rich plasma - Xu, Yongjun; Zhu, Haifeng; Feng, Jian; Shen, Bin (Vojnosanitetski pregled, 2026)
Background/Aim. Chronic refractory wounds are hard-to-heal lesions that are susceptible to bacterial and other pathogenic infections, leading to additional tissue damage and a significant reduction in patients’ quality of life. The aim of this study was to examine the efficacy of nano platelet-rich plasma (PRP) – nano-PRP compared with conventional PRP in the clinical treatment of wounds. Methods. The study included a total of 96 patients with chronic refractory wounds, including wounds caused by trauma and pressure ulcers, admitted between June 2021 and June 2023. According to the treatment applied, the patients were divided into two groups: the observation group (OG) (n = 47) with nano-PRP treatment and the control group (CG) (n = 49) with conventional PRP treatment. Group differences were analyzed using independent-samples t-tests for continuous variables and Chi-square tests for categorical variables. Results. The overall treatment efficacy in the OG was significantly higher than that in the CG (p < 0.05). After treatment, the visual analog scale score decreased in both groups compared with baseline, with the OG showing significantly lower scores than the CG (p < 0.05). The wound healing rate was also significantly higher in the OG (p
Keywords: platelet-rich plasma; quality of life; treatment outcome; wound healing; wounds and injuries